2022
DOI: 10.3390/molecules27238472
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Nutritional Value, and Acceptance of Nut Bars with the Addition of Edible Insect Powder

Abstract: Six types of nut-based bars with the addition of edible insect flour were obtained. Flours made from three different insects (Tenebrio molitor L., Acheta domesticus L., Alphitobius diaperinus P.) were used at two different additive levels (15% and 30%) in relation to the weight of the nuts. The addition of insect flour significantly increased protein content and the insoluble fraction of dietary fiber. The largest amount of these compounds was found in bars with 30% cricket flour, 15.51 g/100 g and 6.04 g/100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Additionally, extruded snacks enriched with mealworm flour contained higher amounts of the essential trace mineral, selenium (García‐Segovia et al, 2020). The addition of insect flour into nut bars concluded that the sensory acceptability of the enriched bars depended on the type of insect flour used where bars supplemented with buffalo worm flour or cricket flour rated higher than those supplemented with mealworm flour (Kowalski et al, 2022b). The higher ratings for the buffalo worm flour or cricket flour enriched bars were attributed to high concentrations of butanol and furfural which imparted a chocolate and caramel taste to the nut bars (Kowalski et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, extruded snacks enriched with mealworm flour contained higher amounts of the essential trace mineral, selenium (García‐Segovia et al, 2020). The addition of insect flour into nut bars concluded that the sensory acceptability of the enriched bars depended on the type of insect flour used where bars supplemented with buffalo worm flour or cricket flour rated higher than those supplemented with mealworm flour (Kowalski et al, 2022b). The higher ratings for the buffalo worm flour or cricket flour enriched bars were attributed to high concentrations of butanol and furfural which imparted a chocolate and caramel taste to the nut bars (Kowalski et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of insect flour into nut bars concluded that the sensory acceptability of the enriched bars depended on the type of insect flour used where bars supplemented with buffalo worm flour or cricket flour rated higher than those supplemented with mealworm flour (Kowalski et al, 2022b). The higher ratings for the buffalo worm flour or cricket flour enriched bars were attributed to high concentrations of butanol and furfural which imparted a chocolate and caramel taste to the nut bars (Kowalski et al, 2022b). Wheat bread enriched with mealworm flour or cricket flour were found to have the best dough properties and final product characteristics compared to other insect flours (Kowalski et al, 2022a).…”
mentioning
confidence: 99%
“…Analysis of volatile compounds in the pasta samples was carried out using the HER-ACLES II electronic nose (Alpha MOS, Toulouse, France) according to the procedure described by Kowalski et al [22].…”
Section: Analysis Of Volatile Compounds Using An Electronic Nosementioning
confidence: 99%
“…Instrumental taste analysis of the pasta samples was performed using an Alpha MOS ASTREE II electronic tongue (Alpha MOS., Toulouse, France) with seven liquid sensors according to Kowalski et al [22].…”
Section: Taste Analysis Using An Electronic Tonguementioning
confidence: 99%
“…It is estimated that by 2050 the world population will reach 10 billion, which is a huge challenge for all sectors involved in food production [45]. Alternatives to existing food products, such as edible insects, can partly address this problem by diversifying food sources, as well as providing high-quality dietary protein [22,23,24,59].…”
Section: Factors Influencing Food Safetymentioning
confidence: 99%